2003
DOI: 10.1097/00001888-200310001-00026
|View full text |Cite
|
Sign up to set email alerts
|

The Privileged Status of Prestigious Terminology: Impact of ???Medicalese??? on Clinical Judgments

Abstract: The specific words used to describe a feature or condition can have an impact on judgments of likelihood of disease, and, to a lesser extent, judgments of seriousness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 3 publications
3
14
0
Order By: Relevance
“…If such simple linguistic phenomena, such as ease of pronunciation, or having English language versus Latinate-sounding terminology in medicine (Eva et al, 2001;Norman et al, 2003;Young et al, 2008), can consistently influence our decisions regarding safety, severity, and care-seeking behavior, it offers caution for public communication and presentation of health information. Tasso et al (2014) warned against the use of drug names that suggested their expected outcome because they were perceived as more effective and less risky than names that had no meaning or alluded to the target health issue.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…If such simple linguistic phenomena, such as ease of pronunciation, or having English language versus Latinate-sounding terminology in medicine (Eva et al, 2001;Norman et al, 2003;Young et al, 2008), can consistently influence our decisions regarding safety, severity, and care-seeking behavior, it offers caution for public communication and presentation of health information. Tasso et al (2014) warned against the use of drug names that suggested their expected outcome because they were perceived as more effective and less risky than names that had no meaning or alluded to the target health issue.…”
Section: Discussionmentioning
confidence: 99%
“…Further, information on the Internet is not always reliable (Diaz et al, 2002), frequently includes multiple possible diagnoses that range in severity, and diseases are often presented in technical or medical terminology (e.g. "medicalese"; Eva et al, 2001;Norman et al, 2003;Young et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations